Bioplastics value chain and blockchain: reducing transaction costs - Eduarda Lara Mendonça Moreira; Andrei Domingues Cechin (RAUSP Management Journal)
Purpose – This paper aims to identify and explain the main transaction costs (TCs) in the second-generation bioplastics value chain and to propose the insertion of blockchain technology to reduce TCs. Design/methodology/approach – It is a holistic single case study of a firm that produces a bioplastic resin made from açaí seeds residues. It analyzed transactions occurred between input supplier (cooperative) and resin factory and between resin factory and transformation industry. Findings – Dominant TCs result from monitoring specific attributes of pretreated açaí seeds and biopolymers, supplier selection, environmental purchasing, time and place specificity, quality control management and technological specificity. Research limitations/implications – Blockchain can potentially reduce TCs by enhancing trust, transparency, material traceability and information exchange. Practical implications – Blockchain can support the further development and commercialization of genuine biodegradable bioplastics by assuring product quality and functioning as a distributed database for stakeholders, minimizing a specific type of opportunism: “greenwashing”. Social implications – This study can help create metrics and policies to achieve the United Nations’ Sustainable Development Goal related to consumption and production patterns by doing better with less and increasing resource efficiency while contributing to strengthening Brazil’s circular (bio)economy. Originality/value – This study’s originality lies in framing the most important challenges regarding TCs in developing bioplastics chains, which can be significantly reduced using a particular distributed database technology.